Sound-Evoked Responses in the Vestibulo-Ocular Reflex Pathways of Rats - Chen, Tianwen; Huang, Jun; Yu, Yue; Tang, Xuehui; Zhang, Chunming; Xu, Youguo; Arteaga, Alberto; Allison, Jerome; Mustain, William; Donald, Matthew C.; Rappai, Tracy; Zhang, Michael; et al. (Frontiers in Neuroscience, 2021)
Vestibular evoked myogenic potentials (VEMP) have been used to assess otolith function in clinics worldwide. However, there are accumulating evidence suggesting that the clinically used sound stimuli activate not only the otolith afferents, but also the canal afferents, indicating canal contributions to the VEMPs. To better understand the neural mechanisms underlying the VEMPs and develop discriminative VEMP protocols, we further examined sound-evoked responses of the vestibular nucleus neurons and the abducens neurons, which have the interneurons and motoneurons of the vestibulo-ocular reflex (VOR) pathways. Single unit recordings and eye movement recording were made from Sprague-Dawley or Long-Evans rats. Air-conducted clicks (50-80 dB SL re ABR threshold, 0.1 ms duration) or tone bursts (60-80 dB SL, 125Hz-4000Hz, 8ms duration, 1ms rise/fall) were delivered to the ears through insert earphones. Among 425 vestibular nucleus neurons recorded in anesthetized rats and 18 abducens neurons recorded in awake rats, sound activated 35.9% of the vestibular neurons that increased discharge rates for ipsilateral head rotation (Type I neuron), 15.7% of the vestibular neurons that increased discharge rate for contralateral head rotation (Type II neuron), 57.2% of the vestibular neurons that did not change discharge rate during head rotation (non-canal neuron), and 38.9% of the abducens neurons. Sound sensitive vestibular nucleus neurons and abducens neurons exhibited characteristic tuning curves that reflected convergence of canal and otolith inputs in the VOR pathways. Tone bursts evoked well-defined eye movements that increased with tone intensity and duration and exhibited peak frequency of ~1500Hz. For the left eye, tone bursts evoked upward/rightward eye movements for ipsilateral ear stimulation, and downward/leftward eye movements for contralateral ear stimulation. These results demonstrate that sound stimulation results in activation of the canal and otolith VOR pathways that can be measured by eye tracking devices to develop discriminative tests of vestibular function in animal models and in humans.